Investigating the association of room features with healthcare-facility–onset Clostridioides difficile: An exploratory study. (2nd July 2021) - Root, Elisabeth Dowling; Lindstrom, Megan; Xie, Amy; Mangino, Julie E.; Moffatt-Bruce, Susan; Hebert, Courtney
Abstract: Objective: To investigate hospital room and patient-level risk factors associated with increased risk of healthcare-facility–onset Clostridioides difficile infection (HO-CDI). Design: The study used a retrospective cohort design that included patient data from the institution's electronic health record, existing surveillance data on HO-CDI, and a walk-through survey of hospital rooms to identify potential room-level risk factors. The primary outcome was HO-CDI diagnosis. Setting: A large academic medical center. Patients and participants: All adult patients admitted between January 1, 2015, and December 31, 2016 were eligible for inclusion. Prisoners were excluded. Patients who only stayed in rooms that were not surveyed were excluded. Results: The hospital room survey collected room-level data on 806 rooms. Included in the study were 17, 034 patients without HO-CDI and 251 with HO-CDI nested within 535 unique rooms. In this exploratory study, room-level risk factors associated with the outcome in the multivariate model included wear on furniture and flooring and antibiotic use by the prior room occupant. Hand hygiene devices and fixed in-room computers were associated with reduced odds of a HO-CDI. Differences between hospital buildings were also detected. The only individual patient factors that were associated with increased odds of HO-CDI were antibiotic use and comorbidity score. Conclusion: Combining a hospital-room walk-through data collection survey, EHR data, and CDI surveillance data, we were able to develop a model to investigate room and patient-level risks for HO-CDI.